2014
DOI: 10.3389/fnins.2014.00182
|View full text |Cite
|
Sign up to set email alerts
|

A lifetime of neurogenesis in the olfactory system

Abstract: Neurogenesis continues well beyond embryonic and early postnatal ages in three areas of the nervous system. The subgranular zone supplies new neurons to the dentate gyrus of the hippocampus. The subventricular zone supplies new interneurons to the olfactory bulb, and the olfactory neuroepithelia generate new excitatory sensory neurons that send their axons to the olfactory bulb. The latter two areas are of particular interest as they contribute new neurons to both ends of a first-level circuit governing olfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(163 citation statements)
references
References 153 publications
(198 reference statements)
7
139
1
4
Order By: Relevance
“…Compartmentalization as a basic feature of the transduction machinery in rods could also be a characteristic of other sensory neurons, such as cones (38,43) and olfactory sensory neurons (44)(45)(46)(47) and could explain the high turnover and renewal of these cells. Not only sensory neurons, which have an intrinsic functional specialization, are likely to be compartmentalized but possibly the great majority of cells have a similar internal organization.…”
Section: Discussionmentioning
confidence: 99%
“…Compartmentalization as a basic feature of the transduction machinery in rods could also be a characteristic of other sensory neurons, such as cones (38,43) and olfactory sensory neurons (44)(45)(46)(47) and could explain the high turnover and renewal of these cells. Not only sensory neurons, which have an intrinsic functional specialization, are likely to be compartmentalized but possibly the great majority of cells have a similar internal organization.…”
Section: Discussionmentioning
confidence: 99%
“…Information on age effects on neurogenesis in the olfactory system has not received as much attention as for the hippocampus (but see the review in Brann and Firestein 2014). Although, in 1997, Tropepe, van der Kooy, and colleagues reported that the aging subventricular zone (SVZ) contained fewer precursor cells than in younger rats (Tropepe et al 1997), only in 2004 was a direct in vivo study published (Enwere et al 2004).…”
Section: Age Effects On Adult Neurogenesismentioning
confidence: 99%
“…The OSNs are true neurons (Golgi type I) that have the unique property of being continuously renewed by neurogenesis, a process involving the cycle of birth, maturation, and death (7). As a consequence of continuous neurogenesis, the olfactory epithelium contains OSNs at different stages of maturation, while the number of live OSNs at any given time is a result of the balance between the rates of their generation and death (7).…”
Section: In Vivo Imaging With Petmentioning
confidence: 99%